Efficiency of adipose derived mesenchymal stem cells on regeneration of facial nerve neurotmesis in Rabbits - Wissam Abdullah Yousif Alhayani; Ahmed I. Abdelglil; Faisal A. Torad; Laila A. Rashed (Cairo : Wissam Abdullah Yousif Alhayani, 2018)
The aim of this study was to evaluate the efficiency of polyglycolic acid mesh and the polyglycolic acid mesh seeded with adipose derived stem cells as a conduit and compared it with control group for regeneration of facial nerve defect in rabbits. A 24 healthy adult rabbits were randomly divided into three equal groups (n=8). In the group A, a 0.5 cm of left buccal branch facial nerve was transected andcoaptated using polyglycolic acid mesh conduit only. In group B, a 0.5 cm of left buccal branch facial nerve was transected andcoaptated using polyglycolic acid mesh seeded with adipose derived stem cells (ADSCs). In group C (control), a 0.5 cm of left buccal branch facial nerve was transected and left without anastomosis.Clinical,histomorphometric, gross pathological, histopathological and electron microscopical evaluations were done. The result showed that, the polyglycolic acid mesh and the polyglycolic acid mesh seeded with adipose derived stem cells enhanced nerve healing across nerve defect and polyglycolic acid mesh seeded with adipose derived stem cells provides better and significant improvement in facial nerve regeneration in rabbits than empty polyglycolic acid mesh conduit and no regeneration was occurred in control group
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Surgery - Anesthesiology and Radiology
Issued also as CD
Keywords: Adipose-derived stem cells; Facial nerve defect; Polyglycolic acid mesh